Physical activity in older cancer patients: evidence and clinical implications - Yajima, Shugo; Kobayashi, Shin; Hashimoto, Tadayoshi; Masuda, Hitoshi (Frontiers in Oncology, 2025)
This mini-review examines the role of physical activity in older cancer patients based on current evidence. As cancer incidence increases with age, older patients face unique challenges including comorbidities and functional decline. This review synthesizes findings regarding physical activity’s impact on cancer prevention, post-operative recovery, and long-term outcomes in older adults. Evidence consistently demonstrates that moderate physical activity reduces risk for several cancers, improves post-surgical recovery, and enhances quality of life while potentially improving survival in cancer survivors. We also address the independent risks of sedentary behavior and briefly discuss alternative forms of physical activity such as yoga and tai chi that may be suitable for older adults. While optimal exercise regimens for specific populations remain under investigation, this review provides evidence-based guidance for incorporating physical activity across the cancer care continuum, emphasizing approaches that account for age-related considerations and functional status of older adults.